The Submaximal Clinical Exercise Tolerance Test (SXTT) to Establish Safe Exercise Prescription Parameters for Patients with Chronic Disease and Disability - Gappmaier, Eduard (Cardiopulmonary Physical Therapy Journal, Inc., 2012)
PURPOSE: To describe how to perform a Submaximal Clinical Exercise Tolerance Test (SXTT) as part of an exercise evaluation in the physical therapy clinic to determine an appropriate exercise prescription and to establish safety of exercise for physical therapy clients. SUMMARY OF KEY POINTS: Physical activity is crucial for general health maintenance. An exercise evaluation includes a comprehensive patient history, physical examination, exercise testing, and exercise prescription. The SXTT provides important clinical data that form the foundation for an effective and safe exercise prescription. Observations obtained during the exercise evaluation will identify at-risk patients who should undergo further medical evaluation before starting an exercise program. Two case examples of SXTTs administered to individuals with multiple sclerosis are presented to demonstrate the application of these principles. STATEMENT OF RECOMMENDATIONS: Due to their unique qualifications, physical therapists shall assume responsibility to design and monitor safe and effective physical activity programs for all clients and especially for individuals with chronic disease and disability. To ensure safety and efficacy of prescribed exercise interventions, physical therapists need to perform an appropriate exercise evaluation including exercise testing before starting their clients on an exercise program.